Changes in Serum Alkaline Phosphatase, Calcium, and Parathyroid Hormone with Different Doses of Iodine Therapy : - Movahedi, Mohammad Mehdi; Atefi, Mohammad; Karimaghaei, Gholam Reza; Noori, Ahmad; Mahmoudi, Tahereh; Gheisari, Farshid (Galen Medical Journal, 2022)
Background: Despite the benefits of radioactive iodine (RAI) therapy as an adjunctive treatment for thyroid cancer, it can be associated with several side effects. The main purpose of this study was to determine the changes in serum alkaline phosphatase (ALP), calcium (Ca), and parathyroid hormone (PTH) at different doses of RAI therapy among patients who were referred to the nuclear medicine department of Namazi Hospital, Shiraz. Materials and Methods: This cross-sectional study was conducted on 60 patients with papillary thyroid cancer who underwent RAI therapy at different doses of 100, 150, and 200 mCi. The ALP, Ca, and PTH levels of patients were measured before and 60 days after RAI therapy. Results: Our study revealed that RAI therapy at all doses significantly increased ALP level in comparison with baseline amounts (Pâ‰¤0.05). However, changes in PTH and Ca levels were not significant among patients who received different doses of RAI (PËƒ0.05). Conclusion: RAI therapy could affect important hormones and enzymes such as ALP and PTH. This issue can be considered in diagnostic and therapeutic prescriptions of RAI for the treatment of thyroid cancer.